Validitas E-Book Berbasis Problem Based Learning pada Materi Perubahan Lingkungan - Harvareza, Dina; Rosba, Evrialiani; Susanti, Diana (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Development of science and technology in the recent periode periode cannot be avoided, its influence on the world of education, including the development of teaching materials. E-Books are one of the teaching materials that can be used in supporting the learning process. The purpose of this research is to produce a valid Problem Based Learning E-Book. This research was conducted at PGRI University, West Sumatra and SMA Negeri 1 Padang Sago using the 4D model (Define, Design, Development, and Disseminate). This research was carried out until the Development stage. The assessment instrument used is a validation sheet that contains the evaluation sheets with 5 evaluation apeks namely content validity, language, presentation, graphic validity and Problem Based Learning syntax compatibility. The data obtained were analyzed by descriptive quantitative. Based on the results of the validity obtained from material experts, media experts, and biology teachers, it shows an average score of 88% of viewed content validity was 89% gained, skill gained 89%, presentation gained 88%, graphics gained 87%, and the Problem Based Learning stage achieved 87%. From these results, it can be concluded that the resulting Problem Based Learning E-Book is very valid.